Theoretical and experimental study on an innovative seismic retrofit solution for old brick masonry buildings. (15th December 2020) - Shi, Sheng; Du, Dongsheng; Xu, Weizhi; Wang, Shuguang
Highlights: An innovative seismic retrofit solution for old masonry buildings is proposed. Both theoretical analysis and shaking-table tests are conducted for verification. The proposed retrofit scheme is proved to be superior than traditional ones. The after-test seismic performance of the proposed scheme is analyzed. Abstract: An innovative retrofit scheme is proposed for the strengthening of old brick masonry buildings: the floor area is increased using newly added and isolated upper stories, and the lower brick masonry part is strengthened using precast concrete wall panels. To investigate the seismic performance of the innovative proposed strengthening scheme, a theoretical analysis and shaking-table tests were conducted, and the proposed scheme is compared with two conventional retrofitting schemes. The results of linear and nonlinear analyses of the three strengthening schemes indicated that all three schemes can mitigate seismic damage to old brick masonry buildings. The shaking-table tests confirmed that the proposed scheme is more effective than the two conventional schemes. Additionally, the seismic performance of the proposed strengthening scheme with post-test damage is investigated via a theoretical analysis and shaking-table tests. The results revealed that the stiffness degradation of the substructure can negatively affect the adding-story isolation system.